Morphometric analysis of ovarian follicles of Black Bengal goats during winter and summer season - Bari, MA; Kabir, ME; Sarker, MB; Khan, AHNA; Momiruzzaman, M (Bangladesh Journal of Animal Science, 2012)
The present study was undertaken to know the development and degeneration of ovarian follicles in Black Bengal does during winter and summer season. Seven ovaries were collected in each season from a local slaughter house. The ovaries were fixed in 10% formalin for histological examination. The numbers of different types of follicles obtained during winter and summer season were compared. To compare two sets of data during winter and summer season, independent t-test was performed using Statistical Package for Social Science (SPSS). Histological examination revealed that mean number of antral follicles per ovary was 34 ± 10 (n=7) in winter which was higher (P<0.05) than those in summer (19±2; n=7) season. The number of secondary follicles per ovary was also higher (P<0.05) in winter (52±5) than summer (35±10) season. During summer season, the ovaries contained 19±4% primary and 71±4% primordial follicles whereas these values were 52±3% and 20±1%, respectively during winter season. The results indicate that lower rate of development and higher rate of degeneration were occurred in goat ovaries during summer than winter season. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10791 Bang. J. Anim. Sci. 2011.39 (1-2): 51-55